Clinical Course, Prognosis, and Cause of Death in Primary Sjögren’s Syndrome - Ildiko Fanny Horvath; Antonia Szanto; Gabor Papp; Margit Zeher (Journal of Immunology Research)
The aim of this retrospective, single-centre study was to investigate the clinical and laboratory features and disease outcomes of 547 patients diagnosed with primary Sjögren’s syndrome (pSS) between 1975 and 2010. The patients were followed up for 11.4±6.2 years. We evaluated the clinical and laboratory features, and assessed their influence on the time of diagnosis, survival, and mortality ratios, and compared them within subgroups defined by gender, glandular and extraglandular manifestations (EGMs), associated diseases, and immunoserological abnormalities. The most frequent EGMs were polyarthritis, Raynaud’s phenomenon, and vasculitis among our patients; the most common associated disease was thyroiditis. During the follow-up period, 51 patients died; the median survival time was 33.71 years. Our results revealed a negative effect of cryoglobulinemia on survival ratios; additionally, the presence of vasculitis and lymphoproliferative diseases at the time of diagnosis increased the risk of mortality. The development of vasculitis was the most powerful predictor of mortality. Mortality in the group of patients with extraglandular symptoms was two- to threefold higher than in the glandular group. Attention is drawn to the importance of close monitoring and targeted diagnostic approaches in those pSS subgroups with obviously increased mortality risk.